METFORMIN VERSUS PHARMACOLOGIC AND NON-PHARMACOLOGIC INTERVENTIONS IN PCOS: A REVIEW OF METABOLIC AND ANTHROPOMETRIC OUTCOMES - Martyna Bukowiec; Karolina Szałata; Laura Magdalena Sikorska; Paulina Pudło; Anna Koman; Monika Czekalska; Weronika Worosz; Luiza Łabuzińska; Angela Ćwil; Mikołaj Asztabski (International Journal of Innovative Technologies in Social Science, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine and metabolic disorder in reproductive age women, marked by insulin resistance, hyperandrogenism, menstrual irregularities, and increased cardiometabolic risk. This review synthesizes current evidence on the clinical effectiveness of metformin versus alternative strategies across anthropometric, glycemic, and lipid outcomes in women with PCOS. This narrative review synthesizes secondary data from systematic reviews and meta-analyses retrieved from PubMed and Google Scholar, comparing metformin with other interventions in reproductive-age women with PCOS across anthropometric, glucose, or lipid outcomes. Metformin showed modest benefits in reducing body mass index, body weight, and waist circumference, with greater effects in overweight and obese individuals. Combined therapies, especially with glucagon-like peptide-1 receptor agonists, were more effective than metformin alone. In glucose metabolism, metformin outperformed placebo and oral contraceptives in reducing fasting glucose, fasting insulin, and homeostatic model assessment of insulin resistance, especially in women with higher insulin resistance. Effects on lipid profiles were moderate; metformin lowered total cholesterol, low-density lipoprotein cholesterol, and triglycerides, particularly when combined with statins. Its effect on high-density lipoprotein cholesterol was limited and sometimes less favorable than that of oral contraceptives. Metformin remains a core treatment in PCOS, with consistent, modest benefits across metabolic and anthropometric domains. Its effectiveness improves when matched to patient profiles and combined with other agents or lifestyle changes.